IDEAL CARDIOVASCULAR HEALTH STATUS AND HEALTH-RELATED QUALITY OF LIFE IN ADOLESCENTS: THE LABMED PHYSICAL ACTIVITY STUDY - César Agostinis-Sobrinho; André de Oliveira Werneck; Justina Kievišienė; Carla Moreira; Robinson Ramírez-Vélez; Rafaela Rosário; Sigute Norkiene; Luís Lopes; Jorge Mota; Rute Santos
ABSTRACT Objective: Adolescent's ideal cardiovascular health index (ICVH) seems to be an important indicator of youth's lifestyles and cardiometabolic health with potential positive consequences for their Health-Related Quality of Life (HRQoL). The purpose of this study was to examine the associations between the ICVH index and HRQoL in adolescents. Methods: This was a cross-sectional study based on secondary analyses from the LabMed Physical Activity Study (n=407 adolescents, 53% girls). ICVH, as defined by the American Heart Association, was determined as meeting ideal behaviors (physical activity, body mass index, smoking status, and diet intake) and health factors (blood pressure, total glucose, and cholesterol). HRQoL was measured with the Kidscreen-10 self-report questionnaire. Results: Analysis of covariance (ANCOVA) showed a significant association between the accumulation of ideal cardiovascular health metrics and HRQoL (F(4,403)=4.160; p=0.003). In addition, the higher the number of ideal health behaviors accumulated, the higher the mean values of HRQoL (p-value for trend=0.001), after adjustments for age, sex, socioeconomic status and pubertal stage. Conclusions: ICVH index was positively associated with HRQoL in adolescents. Ideal health behaviors metrics seem to have a stronger association with HRQoL than the ideal health factors metrics in adolescents.